Hypereosinophilic dermatitis: generalised lichenification and gyrate erythema as the sole manifestation of idiopathic hypereosinophilic syndrome. Issue 10 (15th October 2019) - Yadav, Deepika; Sharma, Ananya; Agarwal, Shipra; Gupta, Vishal
Abstract : A 22-year-old female presented with generalised lichenification and severe pruritus, along with multiple annular papules and concentric plaques over trunk and extremities for the last 3 years. Her haematological investigations revealed leucocytosis with peripheral blood eosinophilia and raised serum IgE levels. Skin biopsy showed perivascular and interstitial infiltrate of eosinophils and lymphocytes in the dermis. Bone marrow examination showed myeloid hypercellularity with increased number of eosinophils, but no atypical cells. Cytogenetic studies did not reveal any chromosomal alterations. No systemic involvement was found on imaging. A diagnosis of idiopathic skin-limited hypereosinophilic syndrome was made. She was treated with tapering doses of oral prednisolone and weekly methotrexate with significant improvement in skin lesions and pruritus in 2 months, which was maintained at 7-month follow-up.